“This page faintly stained with / green”: Compost Aesthetics in John Steffler’s That Night We Were Ravenous - Beardsworth, Adam (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (University of New Brunswick, Dept. of English, 2014)
This essay examines how John Steffler’s poetry collection That Night We Were Ravenous (1998) destabilizes the humanist impulse to position the “authentic” subject at the core of ecological concerns by employing a compost aesthetic that enacts the innately fragmented nature of human subjectivity. It contends that, for Steffler, the poem is its own ecosystem, one that sits in precarious balance with the world around it. The poems in this collection are exploratory rather than expository; their attempts to discover the self in nature are as ephemeral, slippery, and paradoxical as the language that gives them life. Instead of declaiming poetry as a resource that will allow a return to a utopian space, Steffler’s ecological poems position the human subject as a composite of usable waste attuned to the precarious chaos of nature.